Making sense of conservation behaviours in Mustang, Nepal - França, C. S. S.; Kyei, E. O.; Aragundi, G. S.; Rutt, R. L. (Banko Janakari, 2019)
Integrated Conservation and Development Projects (ICDPs) have been undertaken in many countries due to expectations of their supporting both natural resource sustainability and livelihoods. However, they have been challenged by critics over the years, who claim that conservation goals take precedence over local development in practice, thereby worsening the vulnerability of resource-dependent people. Nonetheless, one ICDP implemented in Nepal, the Annapurna Conservation Area Project (ACAP), has been largely regarded by researchers and practitioners as an ICDP success case. Under the authority of a conservation-oriented NGO, ACAP, the ICDP engages local communities participatory for resource management. One community within ACAP has been found to have a substantial timber surplus that satisfies conservation goals, but could also become a sizeable and sustainable source of income for local development. We interrogate the rules and practices of timber management in this community to explore the why behind this practice, discussing how modes of environmental governance aimed at producing behaviors to manage natural resources in particular ways (‘environmentalists’) feature in the seemingly conservation-oriented de jure rules and de facto practices and in authority relations in and around the community.